Base-Promoted Three-Component One-Pot Approach to 3-(α,α-Diarylmethyl)indoles via Arylation of 3-Indolylalcohols - Deb, Mohit L.; Borpatra, Paran J.; J. Saikia, Prakash; Baruah, Pranjal K. (Synthesis, 2017)
A base-promoted 3-component one-pot approach to 3-(α,α-diarylmethyl)indoles via arylation of in situ generated 3-indolylalcohols in ethanol–water solvent system is reported. Use of acid catalysts or neutral organocatalysts does not offer the desired product, but furnish bis(indolyl)methanes instead. Electron-rich aromatics such as naphthols and phenols are preferably employed for arylation. The atom economy, use of green solvent, and the multicomponent strategy are the notable features of the reaction.
Keywords: 3-component; 3-indolylalcohols; arylation; naphthols; phenols; alkylideneindolenine